Differential impact cratering of Saturn's satellites by heliocentric impactors. Issue 2 (15th February 2016) - Hirata, Naoyuki
Abstract: Saturnian satellites are thought to have been struck by two different types of impactors: those with heliocentric origins and those with planetocentric origins. Many of the impacts are suggested to come from planetocentric debris, while many crater count studies assume an ecliptic comet origin when determining the ages of the surfaces. To assess the contribution of planetocentric impactors, this study examines the global distribution and apex‐antapex asymmetry of impact craters on Rhea and Iapetus. The results demonstrate that the craters of Rhea (more than 20 km in diameter) and Iapetus (more than 30 km in diameter) show an apex‐antapex asymmetry. This suggests that most of the large craters are formed from heliocentric impacts. In contrast, the craters less than 20 km in diameter seem to show no asymmetry. Possible explanations for this are either planetocentric impactor origins or saturation with impact craters. Key Points: The distribution of impact craters on Rhea and Iapetus The larger craters show an apex‐antapex asymmetry, while the smaller craters show no asymmetry This difference is likely caused by two distinct impactor populations